The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1088/1748-9326/ac4ebe
|View full text |Cite
|
Sign up to set email alerts
|

The future distribution of wetland birds breeding in Europe validated against observed changes in distribution

Abstract: Wetland bird species have been declining in population size worldwide as climate warming and land-use change affect their suitable habitats. We used species distribution models (SDMs) to predict changes in range dynamics for 64 non-passerine wetland birds breeding in Europe, including range size, position of centroid, and margins. We fitted the SDMs with data collected for the first European Breeding Bird Atlas (EBBA1) and climate and land-use data to predict distributional changes over a century (the 1970s–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…SDM forecasts with static covariates and space‐for‐time substitution have accurately predicted future species' distribution for some species, but have performed poorly for others (Araujo et al, 2005 ; Kharouba et al, 2009 ; Pearman et al, 2008 ; Soultan et al, 2022 ). Moreover, even for SDMs that accurately predicted future species distributions, prediction accuracies for sites at which distribution changes occurred were often low suggesting that improvements to forecasting based on SDMs are needed (Briscoe et al, 2021 ; Illán et al, 2014 ; Rapacciuolo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SDM forecasts with static covariates and space‐for‐time substitution have accurately predicted future species' distribution for some species, but have performed poorly for others (Araujo et al, 2005 ; Kharouba et al, 2009 ; Pearman et al, 2008 ; Soultan et al, 2022 ). Moreover, even for SDMs that accurately predicted future species distributions, prediction accuracies for sites at which distribution changes occurred were often low suggesting that improvements to forecasting based on SDMs are needed (Briscoe et al, 2021 ; Illán et al, 2014 ; Rapacciuolo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…SDM forecasts with static covariates and space-for-time substitution have accurately predicted future species' distribution for some species, but have performed poorly for others (Araujo et al, 2005;Kharouba et al, 2009;Pearman et al, 2008;Soultan et al, 2022).…”
Section: Con Cluding Remark Smentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a biotic lag can be inferred by projecting ENMs calibrated on past data to the present day; where distribution shifts are in the direction but not of the magnitude projected it may suggest a contemporary biotic lag (Fig. 2b) (Lewthwaite et al, 2018;Soultan et al, 2022). Such biotic lags can also be quantified in terms of spatial distance (distance of biotic lag; Fig.…”
Section: Application Of Sfts To Climate-biotic Relationships (1) Popu...mentioning
confidence: 99%
“…Particularly, the waterbirds show a high degree of adaptability to these challenges, because they establish new quarters of wintering (Fox et al, 2019). Also, the displacement of the breeding range for some wetland species was documented as a consequence of the changes of the latitudinal temperature and of the corresponding changed pattern of precipitations (Soultan et al, 2022), though the wintering bird communities are tracking the climate change faster than the breeding communities (Lehikoinen et al, 2021). A recent study on the European birds revealed that the rising temperatures are affecting even the morphology of the birds, while some species reduced their body size and other increased it (McLean et al, 2022).…”
Section: Introductionmentioning
confidence: 99%